Strategy for utilizing social media in improving small micro and medium enterprises market share in the era of revolution 4.0 - I Made Artha Budi Susila; I Nyoman Rasmen Adi (Institut Pariwisata dan Bisnis Internasional, 2021)
Currently, digital marketing, known as social media, is widely used as a promotional medium for business people. The growth in the number of social media users today is also seen as an opportunity to take advantage of social media. It can be seen that the purpose of this study is to determine the strategy of using social media, using social media Instagram in Denpasar City. This research focuses on social media marketing which is applied to the ML Gadgets Bali store which is a quality second gadget store in the city of Denpasar. Using a qualitative approach, with a descriptive analysis, this research collects data through interviews, observations, and documentation which are then analyzed using the SWOT analysis technique comparing internal and external factors to determine the IE Matrix with the SWOT Matrix for strategy determination. The results showed that social media marketing for ML Gadgets Bali is in quadrant 1 in the SWOT Matrix, and cell 5 in the IE Matrix. The right strategy is to support aggressive strategies and growth strategies, namely market penetration, increasing sales and profits, and increasing the effectiveness of marketing on social media.